Sistem Pendukung Keputusan Pemilihan Kerjasama Wedding Organizer Dengan Menerapkan Metode ROC Dan WASPAS - Mhd Faiz Zamzah Amirillah Hasibuan; Maringan Sianturi (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
The selection of wedding organizer cooperation is one way to support choosing the right kersama for the development of a company. The election will have a big impact on the company. So in this research aims to provide the best alternative in the selection of kerjsama wedding organizers by using a decision support system. Decision support system is a form of Computer Base Information System (CBIS) that is interactive, flexible, and specifically developed to support problem solving from unstructured management to improve decision making, decision support systems are usually built to support solutions to a problem or to evaluate an opportunity. In this research, the author will use Rank Order Centroid method in weighting and use Weighted Aggregated Sum Product Assessment method for settlement. The benefit that the authors want to achieve in this study is to be able to provide convenience for the company to choose the best choice that will be invited to cooperate. so as to reduce the risk of loss or even increase the profit and trust of consumers or booker wedding organizers